Contradições do Estado Constitucional Brasileiro: uma análise a partir de Hegel e Marx - Berti, Márcio Guedes (2023)
This doctoral thesis aims to present the contradictions of the 1988 Brazilian Constitution. Our work will have a dialectical approach coming from Marx and authors who fol-lowed in his line. In Marxist theory, law and jurisdiction are an expression of the supers-tructure of a given society, contrary to what Hegel said about law as the realization of freedom. Therefore, in a capitalist society where the economic infrastructure is governed by the bourgeoisie, its superstructure will also be bourgeois, and in the Brazilian case it is no different. To highlight this problem, we are guided by the following work structure: in the first part we will expose, for the following parts to follow, how Hegel conceptua-lizes his Philosophy of Law and the question of the State. In the second part of the the-sis, Marx's criticism of Hegel's philosophy of law will be presented, as well as deve-lopments of his ideas by later Marxists, such as the issue of hegemony in Gramsci, reifi-cation in Lukács, the ideological state apparatuses of Althusser, and the criticism of bourgeois law in Pashukanis. In the third part we will apply what we presented in the first two parts of the work to the constitution of Brazil. We will point out how the cons-titution and law remain ideological devices for maintaining an authoritarian State. Our methodology will be a critical and descriptive analysis of the authors and their commen-tators, using authors from philosophy and law.